PENERAPAN MODEL GAME BASED LEARNING “TREASURE HUNT” TERHADAP LITERASI BUDAYA SISWA KELAS V - Ananda Anggoro Putri; Angga Setiawan; Indah Yunitasari (LPPM STAI Muhammadiyah Probolinggo, 2026)
Cultural literacy is an important ability for elementary school students to understand, appreciate, and preserve Indonesia’s cultural diversity. Amid the challenges of globalization, students' limited understanding of local culture may reduce awareness of preserving national identity. Therefore, innovative instructional models are needed to strengthen cultural literacy at the elementary level. This study aims to determine the effect of the Game Based Learning (GBL) “Treasure Hunt” model in IPAS learning on improving the cultural literacy of fifth-grade elementary school students. This research used a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The subjects consisted of fifth-grade students at SDN 1 Surodakan, with 31 students in the experimental class and 29 students in the control class. Data were collected using pretest and posttest instruments and analyzed through normality test, homogeneity test, independent sample t-test, and N-Gain analysis. The results showed that the implementation of Game Based Learning “Treasure Hunt” had a significant effect on students’ cultural literacy. . The independent samples t-test showed a t-value of 13.964 with a significance level of 0.000 (p < 0.05), indicating a statistically significant difference between the experimental and control groups after the intervention. Furthermore, the experimental class achieved an N-Gain score of 68.87% (moderate category), whereas the control class obtained an N-Gain score of −2.11%. Therefore, the Game Based Learning “Treasure Hunt” model is effective for improving students’ cultural literacy in IPAS learning.